Rectangular Electrode Characteristic in Electrodynamic Solid Particle Measurement - Mohd Riduwan, Ghazali (2011)
Electrodynamic sensor was used in process industry because of lower price and robust designed. It is also used to increase the efficiency of energy and raw materials usage and to improve product quality and process efficiency. Three types of electrode are available in particular application such as pin shape, quarter ring shape and ring shape. This paper focused on the investigation of the pin shape structure and the characteristic of the rectangular shape by using different structure sizes of various lengths and with fixed width. Non-instrusive method was applied to the design of rectangular electrode. The characteristic based on sensitivity of electrode and the spatial filtering effect of sensor will be investigated by using different size of electrodes.Then, the model will be proposed and compared with experimental result.